Peningkatan Ketahanan Aus pada Baja Tahan Karat Martensitik 13Cr AISI 410 setelah Proses Austenisasi dan Tempering [Improvement of Wear Resistance of 13Cr AISI 410 Martensitic Stainless Steel after Austenitizing and Tempering Process] - Annisa Siti Apriani; Moch. Syaiful Anwar; Rusnaldy Rusnaldy; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2017)
The turbine blades that were developed from martensitic stainless steel 13Cr are usually operate on high rotation speed in steam power plants and often found to be failures in the material. One of the failure causes is the presence of foreign material that gives the abrasion impact on the surface of the turbine blade. The aim of this study is observed the effect of austenitization and tempering temperatures on the hardness and abrasion resistance of 13Cr martensitic stainless steel. The examinations were carried out i.e. hardness Rockwell C and abrasion resistance. The optimum hardness values obtained on 13Cr martensitic stainless steel which austenitizing at 1050 °C and tempering of 600 °C. The increasing of tempering temperature in the 13Cr stainless steel does not give a linear negative effect on the abrasion resistance of the steel.AbstrakSudu (blade) turbin yang terbuat dari baja tahan karat martensitik 13Cr yang selalu beroperasi pada kecepatan putaran yang tinggi di pembangkit listrik tenaga uap sering ditemukan kegagalan pada material tersebut. Salah satu penyebab kegagalan ini adalah adanya benda asing yang memberikan dampak abrasi pada permukaan sudu turbin. Penelitian ini bertujuan untuk mengamati pengaruh perlakuan panas austenitization dan tempering terhadap kekerasan dan ketahanan abrasi baja tahan karat martensitik 13Cr. Pengujian yang dilakukan adalah uji kekerasan Rockwell C dan uji ketahanan abrasi. Hasil penelitian ini adalah nilai kekerasan optimum ditemukan pada baja tahan karat martensitik 13Cr yang mengalami austenitization pada suhu 1050°C dengan waktu tempering 600°C. Dengan semakin tinggi suhu tempering maka nilai kekerasan baja tahan karat 13Cr semakin turun. Akan tetapi, kenaikan suhu tempering pada baja tahan karat 13Cr tidak memberikan pengaruh negatif secara linier terhadap ketahanan abrasi baja tersebut.